A rare polyniobotungstate-based framework and its structural transformation in a single-crystal-to-single-crystal process induced by iodide ions. Issue 10 (12th February 2016) - Jin, Lu; Li, Xin-Xiong; Zhao, Dan; Li, Hao-Hong; Zheng, Shou-Tian
Abstract : A rare polyniobotungstate-based framework constructed from Lindqvist [Nb3 W3 O19 ] 5− polyanions and mixed-valent copper ions has been made, which can undergo a solid–liquid reaction with KI solution to form a copper halide via a single-crystal-to-single-crystal process. Abstract : The first transition-metal-bridged polyniobotungstate-based 3D framework has been hydrothermally synthesized, which is constructed from bi-[Cu II (en)2 (H2 O)]-decorating [Nb3 W3 O19 ] 5− polyoxoanions linked together by Cu I ions. Interestingly, the 3D polyniobotungstate framework can undergo a solid–liquid reaction with KI solution to generate a 1D copper halide of [Cu(en)2 ][CuI2 ]2 in a single-crystal-to-single-crystal process.